Immunology of uveitis - Caspi, Rachel R.; Dick, Andrew; Forrester, John; Klein, Reinhild; Niederkorn, Jerry Y.; Paulsen, Friedrich; Rosenbaum, James; Wakefield, Denis; Zierhut, Manfred (Springer Berlin Heidelberg, 2016)
Today we are able to differentiate approximately a hundred entities of intraocular inflammations and group them into anatomical types like anterior, intermediate, posterior, and panuveitis. This book will cover most of the reported entities. A few of these entities have highly typical clinical findings, so that the specialist easily may be able to determine the entity, leading to therapy. But a lot of entities develop similarities in their clinical appearance (similar endothelial precipitates, similar chorioretinal infiltrations, similar retinal necrosis) and also similar complications (elevated intraocular pressure, cataract formation, and macular edema).
CRIS-Team Scopus Importer:2022-08-05